The Influence of Leadership Style and Organizational Culture on Employee Performance in the Regional Secretariat of the Malaka Regent's Office, East Nusa Tenggara Province - AMARAL, Mariano Pinto; NEOLAKA, Melkisedek N.B.C.; TODA, Hendrik (Integration: Journal Of Social Sciences And Culture, 2023)
Purpose: This research, conducted at the Regional Secretariat of the Malacca Regent's Office, aims to assess the impact of Leadership Style and Organizational Culture on Employee Performance, both partially and simultaneously.Methodology:The method used in this research is a survey method with a quantitative approach. The data collection method used is the questionnaire method. Data was gathered through a survey of 284 Civil Servants (PNS), selected through simple random sampling. A Likert scale questionnaire was distributed, with 74 responses suitable for analysis.Findings:Multiple linear regression using SPSS version 26 revealed that leadership style (1) and organizational culture (2) individually have a significant positive effect on employee performance. Simultaneously (3), these factors positively and significantly influenced employee performance (F = 25.256, p = 0.000).Implication:The Coefficient of determination (R2) is 0.794, indicating that the combined impact of leadership style and organizational culture strongly influences variations in employee performance at the Malacca Regent's Office Regional Secretariat, accounting for 79.40%. In comparison, other unexamined factors influence 20.60% of this research.